Fluoropolymer Hybrid Composites

The production of fluoropolymer hybrid composites via melt-phase processing addresses the low ionic conductivity issue in LMP battery separators, resulting in high-density films suitable for lithium-ion batteries with improved conductivity and safety.

JP7627405B2Active Publication Date: 2025-02-06SYENSQO SA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2019562310
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-05-12
Filing Date
2018-05-08
Publication Date
2025-02-06
Estimated Expiration
2038-05-08

AI Technical Summary

Technical Problem

Existing lithium metal polymer (LMP) battery separators exhibit low ionic conductivity at temperatures below 80°C, limiting the effectiveness of extrusion techniques and the safety of electrode separation.

Method used

A method for producing fluoropolymer hybrid organic/inorganic composites through melt-phase processing, involving the extrusion of a pre-composite containing a fluoropolymer, poly(alkylene oxide), and optional inorganic fillers, which enhances ionic conductivity and film density.

Benefits of technology

The method results in high-density films with improved ionic conductivity, suitable for use in electrochemical and photoelectrochemical devices, particularly as separators in lithium-ion batteries, offering enhanced performance and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627405000001
    Figure 0007627405000001
  • Figure 0007627405000002
    Figure 0007627405000002
  • Figure 0007627405000003
    Figure 0007627405000003
Patent Text Reader

Abstract

The present invention relates to fluoropolymer hybrid organic / inorganic composites, films comprising said fluoropolymer hybrid organic / inorganic composites, and the use of said films in various applications, particularly electrochemical and photoelectrochemical applications. [Selection diagram] None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to European Patent No. 17305539.3, filed May 12, 2017, the entire contents of which are incorporated herein by reference for all purposes.

[0002] The present invention relates to fluoropolymer hybrid organic / inorganic composites, films comprising said fluoropolymer hybrid organic / inorganic composites, and the use of said films in various applications, particularly electrochemical and photoelectrochemical applications. [Background technology]

[0003] Lithium metal polymer (LMP) batteries are known in the art, where the anode is a Li metal foil and the separator is a solid electrolyte polymer blend of poly(alkylene oxide) and a fluoropolymer, preferably a vinylidene fluoride polymer, incorporating an electrolyte salt.

[0004] These separators are typically obtained by film extrusion. Unfortunately, one of the drawbacks of this technique is the low ionic conductivity of the separators so obtained at temperatures below 80° C.

[0005] The challenge in this field is therefore to increase the ionic conductivity of these separators to make the extrusion technique more attractive, on the one hand, to provide safe separators that ensure good separation of the electrodes. Summary of the Invention [Means for solving the problem]

[0006] It has now been found that the method of the present invention is a flexible and easy alternative to methods known in the art for producing dense films with excellent ionic conductivity, and therefore suitable for use in electrochemical and photoelectrochemical applications, such as separators in electrochemical devices. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] In a first embodiment, the present invention relates to a method for producing a fluoropolymer hybrid organic / inorganic composite [polymer (FH)], said method comprising: (i) at least one metal compound of formula (I) [compound (M)] in the presence of a liquid medium: X 4-m M(OY) m (I) wherein M is a metal selected from the group consisting of Si, Ti and Zr; X and Y are equal or different from each other and at each occurrence and are selected from hydrocarbon radicals optionally containing one or more functional groups; and m is an integer between 1 and 4. a pregel compound [compound (MP)] obtained by at least partial hydrolysis and / or polycondensation of at least one functional fluoropolymer [polymer (FF)] containing at least one hydroxyl group, in the melt phase, preferably by extrusion, to provide a precomposite [precomposite (FP)]; (ii) reacting the pre-complex (FP) provided in step (i) with: - Formula (II): HO-(CH2CHR A O) n -R B (II) (In the formula, R A is a hydrogen atom or a C1-C5 alkyl group, and R B is a hydrogen atom or a -CH3 alkyl group, and n is an integer between 2000 and 40000, preferably between 4000 and 35000, and more preferably between 11500 and 30000. at least one poly(alkylene oxide) (PAO) of at least one metal salt [salt (M)], and - optionally at least one fluoropolymer [polymer (F)], which may be the same or different from the polymer (FF), and - optionally one or more inorganic fillers; providing a composition by mixing with; and (iii) melt-phase processing, preferably extrusion, of the composition provided in step (ii). Includes.

[0008] The pre-composite (FP) provided in step (i) of the process for preparing the composite (FH) of the present invention is typically in the form of pellets. The pre-composite (FP) is preferably post-treated at a temperature preferably above 100° C. and up to 170° C., for a time typically comprised between 10 minutes and 24 hours.

[0009] The composition provided in step (ii) of the process for producing the composite (FH) of the present invention is typically processed in the melt phase using an extruder, preferably a twin screw extruder.

[0010] In a second embodiment, the present invention relates to a fluoropolymer hybrid organic / inorganic composite [composite (FH)].

[0011] The complex (FH) is advantageously obtainable by the method of the invention.

[0012] The complex (FH) is typically in the form of a pellet.

[0013] The complex (FH) typically consists of: - at least one precomplex [precomplex (FP)], - Formula (II): HO-(CH2CHR A O) n -R B (II) (In the formula, R Ais a hydrogen atom or a C1-C5 alkyl group, and R B is a hydrogen atom or a -CH3 alkyl group, and n is an integer between 2000 and 40000, preferably between 4000 and 35000, and more preferably between 11500 and 30000. at least one poly(alkylene oxide) (PAO) of at least one metal salt [salt (M)], - optionally at least one fluoropolymer [polymer (F)], which is the same or different from the polymer (FF), and - optionally, one or more inorganic fillers and preferably consists of these.

[0014] The composite of the invention (FH) is particularly suitable for use in film manufacturing processes.

[0015] Thus, in a third embodiment, the present invention relates to a method for producing a film, said method comprising processing at least one composite (FH) in the melt phase.

[0016] The process for producing a film according to the invention advantageously comprises processing at least one composite (FH) in the melt phase, typically using an extruder, preferably a single screw extruder.

[0017] Films are typically produced by melt phase processing of at least one composite (FH) using film extrusion techniques such as cast film extrusion or blown film extrusion.

[0018] In a fourth embodiment, the invention relates to a film obtainable by the method of the invention.

[0019] The films of the present invention typically comprise, and preferably consist of, at least one composite (FH).

[0020] The films of the present invention are typically high density films.

[0021] For purposes of the present invention, the term "dense" is intended to mean a film that does not contain pores.

[0022] The film of the present invention typically has a thickness comprised between 2 μm and 300 μm, preferably between 5 μm and 100 μm, more preferably between 10 μm and 40 μm.

[0023] In a fifth embodiment, the present invention relates to an electrochemical or photoelectrochemical device comprising at least one film according to the invention.

[0024] The films of the present invention are suitable for use in electrochemical or photoelectrochemical devices.

[0025] Non-limiting examples of suitable electrochemical devices include secondary batteries, preferably lithium ion batteries.

[0026] The films of the invention can be advantageously used for the manufacture of components for electrochemical devices, preferably secondary batteries.

[0027] The films of the present invention are particularly suitable for use as separators for electrochemical devices, preferably secondary batteries, more preferably lithium ion batteries.

[0028] For the purposes of the present invention, the term "fluoropolymer [polymer (F)]" is intended to mean a fluoropolymer comprising repeat units deriving from at least one fluorinated monomer.

[0029] The polymer (F) may further comprise repeat units derived from at least one hydrogenated monomer.

[0030] Polymer (FF) is typically a polymer (F) further comprising repeat units derived from at least one functional monomer containing at least one hydroxyl group [monomer (OH)].

[0031] The polymer (FF) typically comprises repeat units derived from at least one fluorinated monomer and at least one functional monomer comprising at least one hydroxyl group [monomer (OH)].

[0032] By the term "fluorinated monomer" it is intended herein to mean an ethylenically unsaturated monomer that contains at least one fluorine atom.

[0033] By the term "hydrogenated monomer" it is intended herein to mean an ethylenically unsaturated monomer containing at least one hydrogen atom and no fluorine atoms.

[0034] The term "at least one fluorinated monomer" is understood to mean that the fluoropolymer may contain repeat units derived from one or more fluorinated monomers. In the remainder of the text, the expression "fluorinated monomers" is understood for the purposes of the present invention in both the plural and the singular, i.e., they mean both one or more fluorinated monomers as defined above.

[0035] The term "at least one hydrogenated monomer" is understood to mean that the fluoropolymer may contain repeat units derived from one or more hydrogenated monomers. In the remainder of the text, the expression "hydrogenated monomer" is understood for the purposes of the present invention in both the plural and singular forms, that is, they are understood to mean both one or more hydrogenated monomers as defined above.

[0036] The term "at least one monomer (OH)" is understood to mean that the fluoropolymer may contain repeat units derived from one or more monomers (OH). In the remainder of the text, the expression "monomer (OH)" is understood for the purposes of the present invention to mean both the plural and the singular, i.e., one or more monomers (OH) as they are defined above.

[0037] The monomers (OH) of the polymer (FF) may be selected from the group consisting of fluorinated monomers containing at least one hydroxyl group and hydrogenated monomers containing at least one hydroxyl group.

[0038] When the fluorinated monomer contains at least one hydrogen atom, it is referred to as a hydrogen-containing fluorinated monomer.

[0039] If the fluorinated monomer does not contain any hydrogen atoms, it is called a per(halo)fluoromonomer.

[0040] The fluorinated monomer may further contain one or more other halogen atoms (Cl, Br, I).

[0041] Non-limiting examples of suitable fluorinated monomers include, among others: - C3 to C8 perfluoroolefins, such as tetrafluoroethylene and hexafluoropropylene; - C2-C8 hydrogenated fluoroolefins, such as vinylidene fluoride, vinyl fluoride, 1,2-difluoroethylene and trifluoroethylene; - Formula CH2=CH-R f0 (In the formula, R f0 is a C1-C6 perfluoroalkyl group; - chloro- and / or bromo- and / or iodo-C2-C6 fluoroolefins, for example chlorotrifluoroethylene; - Formula CF2=CFOR f1 (In the formula, R f1is a C1-C6 fluoro- or perfluoroalkyl group, for example, CF3, C2F5, C3F7), (per)fluoroalkyl vinyl ethers; - (per)fluoro-oxyalkyl vinyl ethers of CF2=CFOX0, where X0 is a C1-C 12 Alkyl group or C1-C 12 Oxyalkyl group or C1-C containing one or more ether groups 12 (per)fluorooxyalkyl groups, for example, perfluoro-2-propoxy-propyl groups; - Formula CF2=CFOCF2OR f2 (In the formula, R f2 is a C1-C6 fluoro- or perfluoroalkyl group, for example a C1-C6 (per)fluorooxyalkyl group containing one or more ether groups, such as CF3, C2F5, C3F7 or -C2F5-O-CF3; - Formula CF2 = CFOY0 (wherein Y0 is C1 to C 12 Alkyl or (per)fluoroalkyl groups, or C1-C 12 C1-C containing oxyalkyl groups or one or more ether groups 12 (per)fluorooxyalkyl groups, Y0 containing carboxylic or sulfonic acid groups in their acid, and acid halide or salt form; and - Fluorodioxoles, preferably perfluorodioxoles Examples include:

[0042] When the fluorinated monomer is a hydrogen-containing fluorinated monomer, such as vinylidene fluoride, trifluoroethylene, vinyl fluoride, etc., the fluoropolymer comprises repeat units derived from said at least one hydrogen-containing fluorinated monomer and, optionally, at least one other monomer.

[0043] When the fluorinated monomer is a per(halo)fluoromonomer, such as tetrafluoroethylene, chlorotrifluoroethylene, hexafluoropropylene, (per)fluoroalkyl vinyl ether, etc., the fluoropolymer comprises repeat units derived from at least one per(halo)fluoromonomer and at least one hydrogenated monomer.

[0044] Non-limiting examples of suitable hydrogenated monomers include ethylene, propylene, vinyl monomers, such as vinyl acetate, and styrene monomers, such as styrene and p-methylstyrene, among others.

[0045] Polymer (F) preferably comprises more than 25 mol %, preferably more than 30 mol %, more preferably more than 40 mol % of repeat units derived from at least one fluorinated monomer.

[0046] Polymer (F) may comprise more than 1 mol %, preferably more than 5 mol %, more preferably more than 10 mol % of repeat units derived from at least one hydrogenated monomer.

[0047] The polymer (F) preferably comprises repeat units derived from at least one fluorinated monomer selected from the group consisting of vinylidene fluoride (VDF), tetrafluoroethylene (TFE) and chlorotrifluoroethylene (CTFE).

[0048] The polymer (F) is more preferably selected from the group consisting of fluoropolymers comprising repeat units derived from vinylidene fluoride (VDF) and optionally also comprising repeat units derived from at least one fluorinated monomer other than VDF.

[0049] The polymer (F) is preferably: (a) at least 60 mol %, preferably at least 75 mol %, more preferably at least 85 mol % vinylidene fluoride (VDF), and (b) optionally, from 0.1 mol % to 15 mol %, preferably from 0.1 mol % to 12 mol %, more preferably from 0.1 mol % to 10 mol % of a fluorinated monomer selected from the group consisting of vinyl fluoride, chlorotrifluoroethylene (CTFE), hexafluoropropylene (HFP), tetrafluoroethylene (TFE), trifluoroethylene (TrFE), perfluoromethyl vinyl ether (PMVE), and mixtures thereof; It contains repeating units derived from:

[0050] The polymer (F) may be amorphous or semi-crystalline.

[0051] The term "amorphous" as used herein means a polymer (F) having a heat of fusion, measured according to ASTM D3418-08, of less than 5 J / g, preferably less than 3 J / g, more preferably less than 2 J / g.

[0052] The term "semi-crystalline" is intended in this specification to mean a polymer (F) having a heat of fusion, measured according to ASTM D3418-08, of between 10 and 90 J / g, preferably between 30 and 60 J / g, more preferably between 35 and 55 J / g.

[0053] The polymer (F) is preferably semi-crystalline.

[0054] The polymer (FF) preferably comprises at least 0.01 mol %, more preferably at least 0.05 mol %, even more preferably at least 0.1 mol % of repeat units derived from at least one monomer (OH) as defined above.

[0055] The polymer (FF) preferably comprises at most 20 mol %, more preferably at most 15 mol %, even more preferably at most 10 mol %, and most preferably at most 3 mol % of repeat units derived from at least one monomer (OH) as defined above.

[0056] The determination of the average molar percentage of monomer (OH) repeat units in the polymer (FF) can be carried out by any suitable method, in particular by acid-base titration or by NMR.

[0057] The monomer (OH) is typically selected from the group consisting of hydrogenated monomers containing at least one hydroxyl group.

[0058] The monomers (OH) are preferably (meth)acrylic monomers of formula (III) and vinyl ether monomers of formula (IV): TIFF0007627405000001.tif49161 (wherein R1, R2 and R3 are equal to or different from each other and independently represent a hydrogen atom or a C1 to C3 hydrocarbon group; R OH is a C1-C5 hydrocarbon group containing at least one hydroxyl group. is selected from the group consisting of:

[0059] The monomer (OH) is preferably of formula (III) as defined above.

[0060] The monomer (OH) is more preferably of formula (III'): TIFF0007627405000002.tif24161 (wherein R'1, R'2 and R'3 are hydrogen atoms, and R' OH is a C1-C5 hydrocarbon group containing at least one hydroxyl group. It is of the following.

[0061] Non-limiting examples of monomers (OH) include, among others, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxyethylhexyl (meth)acrylate.

[0062] The monomer (OH) is most preferably: - Formula: Hydroxyethyl acrylate (HEA) from TIFF0007627405000003.tif32161; - Formula: TIFF0007627405000004.tif38161 either 2-hydroxypropyl acrylate (HPA); - and mixtures thereof is selected from the group consisting of:

[0063] The polymer (FF) is more preferably: (a') at least 60 mol%, preferably at least 75 mol%, more preferably at least 85 mol% vinylidene fluoride (VDF); (b') optionally, from 0.1 mol % to 15 mol %, preferably from 0.1 mol % to 12 mol %, more preferably from 0.1 mol % to 10 mol % of a fluorinated monomer selected from the group consisting of vinyl fluoride, chlorotrifluoroethylene (CTFE), hexafluoropropene (HFP), tetrafluoroethylene (TFE), trifluoroethylene (TrFE), perfluoromethyl vinyl ether (PMVE), and mixtures thereof; and (c') 0.01 mol % to 20 mol %, preferably 0.05 mol % to 15 mol %, more preferably 0.1 mol % to 10 mol % of at least one (meth)acrylic monomer of formula (III) as defined above. It contains repeating units derived from:

[0064] Compound (M) of formula (I) may contain one or more functional groups on either group X or group Y, preferably on at least one group X.

[0065] When compound (M) of formula (I) as defined above comprises at least one functional group, it is called a functional metal compound [functional compound (M)]; when neither group X nor group Y comprises a functional group, compound (M) of formula (I) as defined above is called a non-functional metal compound [non-functional compound (M)].

[0066] A mixture of one or more functional compounds (M) and one or more non-functional compounds (M) may be used in the process of the present invention, or the functional compounds (M) or the non-functional compounds (M) may be used separately.

[0067] The compound (M) of formula (I) preferably has the formula (IA): R 1 4-m’ M(OR 2 ) m’ (IA) (wherein M is a metal selected from the group consisting of Si, Ti and Zr; R 1 and R 2 are equal or different from each other and from each occurrence, and optionally contain one or more functional groups; 1~ C 18 and m' is an integer between 1 and 4. It is of the following.

[0068] Non-limiting examples of functional groups include epoxy groups, carboxylic acid groups (in acid, ester, amide, anhydride, salt or halide form), sulfonic acid groups (in acid, ester, salt or halide form), hydroxyl groups, phosphate groups (in acid, ester, salt or halide form), thiol groups, amine groups, quaternary ammonium groups, ethylenically unsaturated groups (such as vinyl groups), cyano groups, urea groups, organosilane groups, aromatic groups.

[0069] When the compound (M) of formula (I) is a functional compound (M), it preferably has the formula (IB): R 3 4-m’’ M(OR 4 ) m’’ (IB) (wherein M is a metal selected from the group consisting of Si, Ti and Zr, and R 3 are equal or different from each other and from each occurrence, and contain one or more functional groups, C1 to C 12 is a hydrocarbon group, R 4 are equal or different from each other and from each occurrence, and are C1 to C5 linear or branched alkyl groups, preferably R4 is a methyl or ethyl group, and m'' is an integer between 2 and 3. It is of the following.

[0070] Examples of functional compounds (M) are in particular vinyltriethoxysilane, vinyltrimethoxysilane, vinyltrismethoxyethoxysilane of formula CH2=CHSi(OC2H4OCH3)3, vinyltrismethoxyethoxysilane of formula: 2-(3,4-epoxycyclohexylethyltrimethoxysilane) from TIFF0007627405000005.tif22161, formula: glycidoxypropylmethyldiethoxysilane, formula: Glycidoxypropyltrimethoxysilane in TIFF0007627405000006.tif22161, formula: Methacryloxypropyltrimethoxysilane in TIFF0007627405000007.tif22161, formula: Aminoethylaminopropylmethyldimethoxysilane from TIFF0007627405000008.tif22161, formula: H2NC2H4NHC3H6Si(OCH3)3 aminoethylaminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-phenylaminopropyltrimethoxysilane, 3-chloroisobutyltriethoxysilane, 3-chloropropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, n-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane, (3-acryloxypropyl)dimethylmethoxysilane, (3-acryloxypropyl)methyldichlorosilane, (3-acryloxypropyl)methyldimethoxysilane, 3-(n-allylamino)propyltrimethoxysilane, 2-(4-chlorosulfonylphenyl)ethyltrimethoxysilane, 2-(4-chlorosulfonylphenyl)ethyltrichlorosilane, carboxyethylsilanetriol, and its sodium salt, the formula: Triethoxysilylpropylmaleamic acid from TIFF0007627405000009.tif22161, 3-(trihydroxysilyl)-1-propane-sulfonic acid of the formula HOSO2-CH2CH2CH2-Si(OH)3, N-(trimethoxysilylpropyl)ethylene-diaminetriacetic acid, and its sodium salt of the formula: TIFF0007627405000010.tif35161 3-(triethoxysilyl)propylsuccinic anhydride, Acetamidopropyltrimethoxysilane of formula H3C-C(O)NH-CH2CH2CH2-Si(OCH3)3, formula Ti(A) X (OR) Y where A is an amine substituted alkoxy group, such as OCH2CH2NH2, R is an alkyl group, and x and y are integers such that x+y=4.

[0071] Examples of non-functional compounds (M) are in particular trimethoxysilane, triethoxysilane, tetramethoxysilane, tetraethoxysilane (TEOS), tetramethyl titanate, tetraethyl titanate, tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, tetra-isobutyl titanate, tetra-tert-butyl titanate, tetra-n-pentyl titanate, tetra-n-hexyl titanate, tetraisooctyl titanate, tetra-n- Lauryl titanate, tetraethyl zirconate, tetra-n-propyl zirconate, tetraisopropyl zirconate, tetra-n-butyl zirconate, tetra-sec-butyl zirconate, tetra-tert-butyl zirconate, tetra-n-pentyl zirconate, tetra-tert-pentyl zirconate, tetra-tert-hexyl zirconate, tetra-n-heptyl zirconate, tetra-n-octyl zirconate, and tetra-n-stearyl zirconate.

[0072] The term "liquid medium" is intended herein to mean a medium that is in the liquid state at 20° C. under atmospheric pressure.

[0073] In step (i) of the process for preparing the complex (FH) of the invention, compound (M) of formula (I) is partially hydrolyzed and / or polycondensed in the presence of a liquid medium, which typically contains water, thereby providing a pre-gel compound [compound (MP)].

[0074] The compound (MP) is typically in the form of a liquid composition, said liquid composition typically comprising water.

[0075] The weight ratio of the compound (M) of formula (I) to the aqueous medium is typically comprised between 50:1 and 1:50, preferably between 20:1 and 1:20, more preferably between 10:1 and 1:10.

[0076] The liquid medium may further comprise at least one acid catalyst.

[0077] The liquid medium further comprises typically from 0.5% to 10% by weight, preferably from 1% to 5% by weight, of at least one acid catalyst.

[0078] The choice of acid catalyst is not particularly limited.

[0079] The acid catalyst is typically selected from the group consisting of organic acids and inorganic acids, and preferably selected from the group consisting of organic acids.

[0080] Very good results were obtained with citric acid.

[0081] The liquid medium may further comprise one or more organic solvents.

[0082] Non-limiting examples of suitable organic solvents include, inter alia: aliphatic, cycloaliphatic or aromatic ether oxides, more particularly diethyl oxide, dipropyl oxide, diisopropyl oxide, dibutyl oxide, methyl tert-isobutyl ether, dipentyl oxide, diisopentyl oxide, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether benzyl oxide, dioxane, tetrahydrofuran (THF), glycol ethers, such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether, ethylene glycol monophenyl ether, ethylene glycol monobenzyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol mono-n-butyl ether; glycol ether esters, such as ethylene glycol methyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, Alcohols, such as methyl alcohol, ethyl alcohol, diacetone alcohol, ketones, such as acetone, methyl ethyl ketone, methyl isobutyl ketone, diisobutyl ketone, cyclohexanone, isophorone, and - linear or cyclic esters, e.g. isopropyl acetate, n-butyl acetate, methyl acetoacetate, dimethyl phthalate, gamma-butyrolactone Includes:

[0083] For embodiments in which the aqueous medium comprises one or more additional organic solvents, the aqueous medium is preferably free of solvents qualified as carcinogenic, mutagenic, or reproductively toxic by chemical safety classification (CMR solvents); more particularly, the aqueous medium is advantageously free of N-methyl-2-pyrrolidone (NMP), N,N-diethylacetamide, dimethylformamide (DMF) and N,N-dimethylacetamide (DMAC).

[0084] The liquid medium preferably further comprises at least one acid catalyst and one or more organic solvents (S).

[0085] The liquid medium more preferably further comprises at least one acid catalyst and one or more alcohols.

[0086] In step (i) of the process for producing the complex (FH) of the invention, the hydrolysis and / or polycondensation of the compound (M) of formula (I) and the polymer (FF) is usually carried out at room temperature or upon heating at a temperature below 100° C. The temperature is selected taking into account the boiling point and / or the stability of the aqueous medium. Temperatures comprised between 20° C. and 90° C., preferably between 20° C. and 50° C., are preferred.

[0087] It is understood that in step (i) of the process for preparing the conjugate (FH) of the invention, the group Y of the compound (M) of formula (I) is partially hydrolyzed or polycondensed in the presence of the polymer (FF) in an aqueous medium, thereby generating a preconjugate [preconjugate (FP)].

[0088] As will be appreciated by those skilled in the art, this will usually result in the production of low molecular weight by-products through hydrolysis and / or polycondensation reactions, which may in particular be water or alcohol, depending on the nature of compound (M) of formula (I) as defined above.

[0089] Thus, in step (i) of the process for producing the conjugate (FH) of the invention, the aqueous medium typically further comprises one or more alcohols.

[0090] Compound (MP) typically has the formula -[O-MX 4-m* (OY) m*-2 ]O- (wherein M is a metal selected from the group consisting of Si, Ti and Zr, X and Y are equal or different from each other and each occurrence and are hydrocarbon radicals optionally containing one or more functional groups, m * is an integer between 2 and 4 inclusive).

[0091] The pre-complex (FP) typically comprises one or more domains of the formula -[OM(OZ1)(OZ2)]O-, where M is a metal selected from the group consisting of Si, Ti and Zr, Z1 and Z2 are equal or different and are hydrocarbon groups optionally comprising one or more functional groups, and at least one of Z1 and Z2 is a hydrocarbon group comprising repeat units derived from at least one monomer (OH).

[0092] In the process for preparing the composite (FH) of the invention, the composition provided in step (ii) is typically processed in the melt phase at a temperature comprised between 100°C and 300°C, preferably between 150°C and 250°C.

[0093] The liquid medium provided in step (i) of the method for producing the composite (FH) of the present invention typically contains 5% by weight to 95% by weight, preferably 20% by weight to 80% by weight, and more preferably 30% by weight to 60% by weight of at least one polymer (FF), based on the total weight of the liquid medium.

[0094] The composition provided in step (ii) of the process for producing the composite (FH) of the present invention may further contain at least one fluoropolymer [polymer (F)], preferably a non-functionalized fluoropolymer [non-functionalized polymer (F)], which is the same as or different from the polymer (FF).

[0095] For the purposes of the present invention, the term "non-functional polymer (F)" is intended to mean a fluoropolymer that does not contain repeat units derived from at least one functional monomer, for example a functional monomer containing at least one hydroxyl group [monomer (OH)].

[0096] The selection of the non-functional polymer (F) is not particularly limited, provided that it does not interact with the precomplex (FP) and / or the PAO of formula (II).

[0097] Polymer (FH) is: - from 30% to 99% by weight, preferably from 50% to 95% by weight, more preferably from 60% to 90% by weight of at least one precomplex (FP) and at least one PAO of formula (II), - from 1% to 70% by weight, preferably from 5% to 50% by weight, more preferably from 10% to 40% by weight of at least one salt (M), - optionally from 1% to 60% by weight, preferably from 5% to 40% by weight, more preferably from 10% to 30% by weight, of at least one polymer (F), identical or different to the polymer (FF), and - optionally 0.1% to 90% by weight of one or more inorganic fillers; Preferably, the composition comprises, more preferably, consists of, These amounts are based on the total weight of the complex (FH).

[0098] The salt (M) is typically supplied either in powder form or as an aqueous solution containing it.

[0099] The nature of the salt (M) is not particularly limited.

[0100] The salt (M) is typically MeI, Me(PF6) n , Me(BF4) n , Me(ClO4) n , Me(bis(oxalato)borate) n ("Me (BOB) n ”), MeCF3SO3, Me[N(CF3SO2)2] n , Me[N(C2F5SO2)2] n , Me[N(CF3SO2)(R F SO2)] n (where R F is C2F5, C4F9 or CF3OCF2CF2), Me(AsF6) n , Me[C(CF3SO2)3] n , Me2S n wherein Me is a metal, preferably a transition metal, alkali metal or alkaline earth metal, more preferably Me is Li, Na, K or Cs, even more preferably Me is Li, and n is the valence of the metal, typically n is 1 or 2.

[0101] The salt (M) is preferably MeCF3SO3, Me[N(CF3SO2)2] n , Me[N(C2F5SO2)2] n , Me[N(CF3SO2)(R F SO2)] n (where R F is C2F5, C4F9 or CF3OCF2CF2), Me(AsF6) n , Me[C(CF3SO2)3] n and Me2S n wherein Me is a metal, preferably a transition metal, alkali metal or alkaline earth metal, more preferably Me is Li, Na, K or Cs, even more preferably Me is Li, and n is the valence of the metal, typically n is 1 or 2.

[0102] When present, inorganic fillers are typically provided in the form of particles.

[0103] The inorganic filler typically has an average particle size comprised between 0.001 μm and 1000 μm, preferably between 0.01 μm and 800 μm, more preferably between 0.03 μm and 500 μm.

[0104] Among the inorganic fillers suitable for use in the present invention, there may be mentioned inorganic oxides, including metal oxides, metal sulfates, metal carbonates, metal sulfides, etc. Among the metal oxides, there may be mentioned SiO2, TiO2, ZnO and Al2O3.

[0105] To the extent that the disclosures of any patents, patent applications, and publications incorporated herein by reference conflict with the statements of this application to the extent that the term may be unclear, this statement shall control.

[0106] The present invention will now be described with reference to the following examples, the purpose of which is merely illustrative and not limiting the scope of the invention. EXAMPLES

[0107] raw materials Polymer (FF-1): VDF-HEA (0.8 mol%)-HFP (2.4 mol%) with a melt flow index (MFI) of 15 g / min (2.16 Kg, 230° C.).

[0108] Polymer (FF-2): VDF-HEA (0.5 mol%)-HFP (2.2 mol%) with a melt flow index (MFI) of 3.1 g / min (10 Kg, 230° C.).

[0109] PAO-1: Poly(ethylene oxide) having an average molecular weight comprised between 1,000,000 and 1,200,000.

[0110] Polymer (1): VDF / HFP (93 mol% / 7 mol%) with a melt flow index (MFI) of 15 g / min (2.16 Kg, 230° C.).

[0111] Ionic conductivity determination The membrane was placed in a cell containing two stainless steel blocking electrodes. The cell was placed in an oven and conditioned at the respective temperature for 1 h before measuring the ionic conductivity. The resistance of the membrane was measured at different temperatures. The ionic conductivity (σ) was calculated according to the following formula: Ionic conductivity [σ] = d / (R b ×S) (where d is the thickness of the film [cm], R b is the bulk resistance [Ω] and S is the area of ​​the stainless steel electrode [cm 2 ]) was used to calculate.

[0112] Production of polymer (FF-1) Into an 80 liter reactor equipped with an impeller operating at a speed of 300 rpm, 58242 g of demineralized water and 11.1 g of METHOCEL® K100 GR suspending agent were successively introduced. The reactor was purged with vacuum (30 mmHg) and nitrogen at 20° C. in turn. Then, 21.6 g of hydroxyethyl acrylate (HEA) and 1873 g of hexafluoropropylene (HFP) monomer were introduced into the reactor, followed by 149.9 g of a 75% by weight solution of t-amyl perpivalate initiator in isododecane. Finally, 16597 g of vinylidene fluoride (VDF) were introduced into the reactor. The reactor was gradually heated to the set point temperature at 57° C. and the pressure was fixed at 110 bar. During the polymerization, the pressure was kept constant at 110 bar by feeding 13 kg of an aqueous solution containing 240.6 g of HEA. After this feeding, no more aqueous solution was introduced and the pressure started to drop to 80 bar. The polymerization was then stopped by venting the reactor until atmospheric pressure was reached. In general, a conversion of almost 75% of the monomers was obtained. The polymer so obtained was then recovered, washed with demineralized water and oven-dried at 65°C.

[0113] Production of polymer (FF-2) In a 4 liter reactor equipped with an impeller operating at a speed of 650 rpm, 2438 g of demineralized water, 90.74 g of a solution of trisodium phosphate with a concentration of 543 mmol / kg, and 59.66 g of an aqueous solution of METHOCEL® K100 GR with a concentration of 14.2 g / kg were successively introduced. The reactor was purged with vacuum (30 mmHg) and then with nitrogen at 14° C. Then, 16.42 g of a 5.1% by weight hydrogen peroxide solution and 5.35 g of ethyl chloroformate were introduced into the reactor. After 15 minutes at a speed of 880 rpm, 25.2 g of an aqueous solution of hydroxyl acrylate (HEA) with a concentration of 17 g / kg HEA and 107 g of hexafluoropropylene (HFP) comonomer were introduced. Finally, 952 g of vinylidene fluoride (VDF) were introduced into the reactor. The reactor was gradually heated to the set point temperature at 45° C. and the pressure was fixed at 120 bar. During the polymerization, the pressure was always kept equal to 120 bar by feeding 605 g of an aqueous solution containing HEA. After this feeding, no more aqueous solution was added and the pressure started to drop. The polymerization was stopped by venting the reactor until atmospheric pressure was reached. A conversion of 72% of the monomers was reached. The polymer so obtained was then recovered, washed with demineralized water and dried overnight at 65° C.

[0114] Production of Complex (FH) – Basic Procedure Preparation of precomplex (FP) A pregel compound was formed as follows: a) In a 500 ml beaker equipped with a magnetic stirrer operating at moderate speed, the following ingredients were introduced in sequence: - TEOS (Tetraethyl orthosilicate): 200g, - Water: 69.45g (molar ratio TEOS:H2O = 1:4), - Ethanol: 50g (weight ratio TEOS:EtOH = 4:1), - Citric acid: 2.69g (1% by weight TEOS+H2O). The theoretical amount of SiO2 produced in each batch is 57.68 g (17.91% of the starting material); and b) The system was left at room temperature for approximately 3 hours with vigorous stirring.

[0115] The polymer (FF) was fed from the main hopper into a twin-screw co-intermeshing extruder (Leistritz 18 ZSE 18 HP with screw diameter D 18 mm and screw length 720 mm (40 D)). The extruder is equipped with a main feeder and two degassing units. The barrel consists of eight temperature control zones and a cooling zone (at the feeder) that can be set to the desired temperature profile. The molten polymer leaves a die consisting of two holes, each with a diameter of 3 mm. The material is subsequently simultaneously pulled by pull rollers and air-cooled immediately before being mechanically chopped into pellets.

[0116] At the same time, the pregel compound was also fed into the extruder through the main hopper. The composition of the precomposite (FP) was determined by the feeding ratio of the polymer (FF) and the pregel compound (see Examples).

[0117] The screw profile for this step consisted of a region of conveying elements with a regular decrease in pitch (from zone 0 to zone 1), then a kneading block made up of two kneading elements (zone 2), then a long conveying zone (from zone 3 to zone 4); after this series of elements, two kneading blocks made up of three kneading elements and alternating with two conveying elements were placed (from zone 4 to zone 6). Finally, four conveying elements and a degassing unit were located before the die exit (from zone 6 to zone 8). The temperature profiles used are reported in table 1 below. Profile A was used for polymer (FF-1) and polymer (FF-2). The extruder rotation speed was 300 rpm. The pellets obtained were aged in an oven at 150° C. for 40 minutes.

[0118] TIFF0007627405000011.tif36170

[0119] Preparation of complex (FH) The precomposite (FP), PAO, and aqueous LiTFSI solution (80 wt%) were fed into the extruder from the main hopper as described below: the pellets and PAO were fed by a gravimetric feeder, and the aqueous LiTFSI solution was fed by a peristaltic pump, respectively.

[0120] The screw profile for this step consisted of a first conveying zone (zone 0 and zone 1) followed by a kneading block (zone 2) formed by three kneading elements; after these blocks there was a long conveying zone (zone 3) where the pitch of the screw was maximum. In this zone there was a degassing unit at atmospheric pressure. Then there was a kneading block composed of two kneading elements and a countercurrent element (zone 5). After this block the screw consisted of a conveying zone with maximum pitch (zone 6); in this zone a degassing unit at -400 mbar was present mainly to evacuate the water vapor present in the LiTFSI solution. The last part of the screw (zone 7 and zone 8) consisted of conveying elements.

[0121] The temperature profile B used is reported below in Table 2. The extruder rotation speed was 350 rpm.

[0122] TIFF0007627405000012.tif36170

[0123] Composite (FH) film extrusion A single screw extruder (Eurotech with screw diameter D25 mm and screw length 75 cm) was used to produce the film. The extruder is equipped with a main feeder. The barrel consists of six temperature control zones set at 140 °C to 180 °C. The molten polymer exits through a 20 cm flat die with an opening of 0.2 mm. The material is subsequently pulled and pressed by a three-calendar system and subsequent rollers. The calenders were heated at 90 °C and two non-sticky support films were fed between the first two calenders, leading to an extruded film of about 30 to 100 μm.

[0124] Example 1 The precomposite (FP) was produced at a rate of polymer (FF-1) of 0.450 Kg / h and a rate of pregel compound of 0.833 Kg / h. The resulting nominal composition was FF-1 / SiO2: 75 / 25 wt%. Complex (FH): Precomplex (FP) 0.525Kg / h, PAO 0.875Kg / h, and LiTFSI aqueous solution 0.4375Kg / h.

[0125] The final composition of the composite (FH) was: 50 wt% PAO, 22.5 wt% polymer (FF-1), 20 wt% LiTFSI, and 7.5 wt% SiO2.

[0126] The ionic conductivity of this material was measured on compression molded films of approximately 100 μm, and the results are shown in Table 3.

[0127] Example 2 The same procedure was followed as detailed in Example 1, except that polymer (FF-2) was used. The results are shown in Table 3.

[0128] Example 3 The same procedure was followed as detailed in Example 1, except that a precomposite made at a rate of 0.525 Kg / h of polymer (FF-1) and 0.417 Kg / h of pregel compound was used. The nominal composition obtained was FF-1 / SiO2: 87.5 / 12.5 wt%.

[0129] The final composition of the composite was: 50 wt% PAO, 26.25 wt% polymer (FF-1), 20 wt% LiTFSI, and 3.75 wt% SiO2. The results are shown in Table 3.

[0130] Example 4 The same procedure was followed as detailed in Example 3, except that a precomposite (FP) obtained from polymer (FF-2) was used. The material was successfully extruded into a 30 μm thick film without the presence of defects, and the results are shown in Table 3.

[0131] Comparative Example 1 Following the general procedure for the preparation of the composites without using a pregel compound, polymer (1), PAO, and LiTFSI were mixed in the following ratio: 50 wt% PAO + 30 wt% polymer (1), and 20 wt% LiTFSI.

[0132] The ionic conductivity of this material was measured on an extruded film of about 150 μm, and the results are shown in Table 3.

[0133] TIFF0007627405000013.tif69170

[0134] Considering the above, it has surprisingly been found that the method of the present invention makes it possible to easily obtain composites (FH) that result in films with superior ionic conductivity compared to state-of-the-art films.

[0135] It has also been surprisingly found that the composites (FH) of the present invention can be easily processed into film separators, typically by cast extrusion. Thus, the method of the present invention successfully enables the manufacture of separators for both electrochemical and photoelectrochemical devices.

Claims

1. A method for producing a fluoropolymer hybrid organic / inorganic composite [composite (FH)], comprising the steps of: (i) at least one metal compound of formula (I) [compound (M)] in the presence of a liquid medium: X 4-m M(OY) m (I) wherein M is a metal selected from the group consisting of Si, Ti, and Zr; X and Y are equal or different from each other and each occurrence and are selected from hydrocarbon groups optionally containing one or more functional groups; and m is an integer between 1 and 4. a pregel compound [compound (MP)] obtainable by at least partial hydrolysis and / or polycondensation of at least one functional fluoropolymer [polymer (FF)] comprising at least one hydroxyl group, in the melt phase to provide a precomposite (Precomposite (FP)); (ii) the precomplex (FP) provided in step (i), - Formula (II): HO-(CH 2 CHR A O) n -R B (-I) (In the formula, R A is a hydrogen atom or C 1 ~C 5 is an alkyl group, R B is a hydrogen atom or -CH 3 alkyl group, and n is an integer between 2000 and 40000. at least one poly(alkylene oxide) (PAO) of at least one metal salt [salt (M)], - optionally at least one fluoropolymer [polymer (F)], identical or different to said polymer (FF), and optionally one or more inorganic fillers, providing a composition by combining with; and (iii) melt phase processing the composition provided in step (ii); The method includes:

2. 2. The method of claim 1, wherein the polymer (FF) comprises at least 0.01 mol % of repeat units derived from at least one monomer (OH).

3. 3. The method according to claim 1 or 2, wherein the polymer (FF) comprises up to 20 mol % of repeat units derived from at least one monomer (OH).

4. The monomer (OH) is a (meth)acrylic monomer of formula (III) and a vinyl ether monomer of formula (IV): (In the formula, R 1 , R 2 and R 3 are equal to or different from each other and are independently a hydrogen atom or C 1 ~C 3 is a hydrocarbon group, R OH C containing at least one hydroxyl group 1 ~C 5 It is a hydrocarbon group. The method according to claim 2 or 3, wherein the compound is selected from the group consisting of:

5. The compound (MP) is represented by the formula -[O-MX 4-m* (OY) m*-2 ]O-, where M is a metal selected from the group consisting of Si, Ti, and Zr, X and Y are equal or different from each other and each occurrence and are hydrocarbon radicals optionally containing one or more functional groups, and m* is an integer in the range from 2 to 4. The method according to any one of claims 1 to 4, in the form of a liquid composition comprising one or more domains of

6. The precomplex (FP) has the formula -[O-M(OZ 1 ) (OZ 2 ) ]O- (wherein M is a metal selected from the group consisting of Si, Ti and Zr, and Z 1 and Z 2 are equal to or different from each other and are hydrocarbon groups optionally containing one or more functional groups, 1 and Z 2 6. The method of claim 1, wherein at least one of said first and second monomers is a hydrocarbon group comprising repeat units derived from at least one monomer (OH).

7. A process for the production of a film, comprising melt-phase processing of the composite (FH) after step (iii) of the process according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Fluoropolymer film

    JP2015520781A

  • Method for manufacturing fluoropolymer hybrid composites

    JP2015537077A

  • dense fluoropolymer film

    JP2016501950A

  • Fluoropolymer hybrid composite

    JP2018537560A